THE INFLUENCE OF WATERMELON JUICE TO A DECREASE IN BLOOD PRESSURE ON THE ELDER HYPERTENSION - Anis Setiyowati; Endang Yuswatiningsih; Anin Wijayanti (Jurnal Keperawatan, 2012)
Hypertension is still the biggest problem for health especially in the elderly .A decrease in the function ofcertain organs on the elderly that causes of hypertension .Hypertension is a condition where increase inblood pressure rapidly and not stable or patients who had blood pressure more than 140 mmhg / 90 .Thisresearch aims to analyse the influence of watermelon juice to a decrease in blood pressure on the elderhypertension . The design of this research is pre analytic experiment with using the approach of one-grouppra-post test design .The population in this research is all for the elderly of hypertension in the village elderposyandu ngudirejo diwek sub-district district jombang with the total sample of respondents as many as 25.Sampling techniques used sample random sampling .The independent variable is watermelon juice , whilethe dependent variable is a decrease in blood pressure on the elder hypertension ..An instrument of thisresearch using sheets of observation with editing data processing , as well , scoring , tabulating .And usingstatistical test wilcoxon . The results of the study shows elderly decreased blood pressure and systoledyastole .Before the provision of watermelon juice average blood pressure of systole 152,8 mmhg anddyastole 88.4 mmhg .While after the provision of watermelon juice systole of blood pressure during adiastole mmhg 138,4 74,8 mmhg .The results obtained wilcoxon test the value of p = 0.0001 & it; 0.05 the h1accepted .Conclusions in this research are no influence to a watermelon to a decrease in blood pressure inthe elderly and hypertension.